Short DNA Fragments Are a Hallmark of Heavy Charged-Particle Irradiation and May Underlie Their Greater Therapeutic Efficacy - Pang, Dalong; Chasovskikh, Sergey; Rodgers, James E.; Dritschilo, Anatoly (Frontiers in Oncology, 2016)
Growing interest in proton and heavy ion therapy has reinvigorated research into the fundamental biological mechanisms underlying the therapeutic efficacy of charged particle radiation. To improve our understanding of the greater biological effectiveness of high-LET radiations, we have investigated DNA double strand breaks (DSB) following exposure of plasmid DNA to low-LET Co-60 gamma photon and electron irradiation and to high-LET Beryllium and Argon ions with atomic force microscopy (AFM). The sizes of DNA fragments following radiation exposure were individually measured to construct fragment size distributions from which the DSB per DNA molecule and DSB spatial distributions were derived. We report that heavy charged particles induce a significantly larger proportion of short DNA fragments in irradiated DNA molecules, reflecting densely and clustered damage patterns of high-LET energy depositions. We attribute the enhanced short DNA fragmentation following high-LET radiations as an important determinant of the observed, enhanced biological effectiveness of high-LET irradiations.